2014
DOI: 10.4236/abcr.2014.32007
|View full text |Cite
|
Sign up to set email alerts
|

Social Support Provided to Women Undergoing Breast Cancer Treatment: A Study Review

Abstract: Breast cancer treatment may have implications for women's quality of life and social support, which refers to mechanisms through which interpersonal relationships protect people from the detrimental effects of stress. This study's objective was to analyze evidence available in the literature concerning social support provided to women with breast cancer undergoing chemotherapy. The Latin American and Caribbean Literature on Health Sciences (LILACS), PubMed, Web of Science, Psycinfo and Cumulative Index to Nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 23 publications
(35 reference statements)
1
11
0
4
Order By: Relevance
“…Researches suggests that problems with sexual functioning are common in women with breast cancer undergoing chemotherapy. (11,21,22) Studies on the quality of life related to health encompass both clinical morbidity caused directly by the disease state, as the influences of disease and treatments on daily activities and satisfaction with life. Intervention strategies can be formulated by evaluating aspects of quality of life related to health, in order to minimize the effects of the disease of progressive character, and improve aspects of quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Researches suggests that problems with sexual functioning are common in women with breast cancer undergoing chemotherapy. (11,21,22) Studies on the quality of life related to health encompass both clinical morbidity caused directly by the disease state, as the influences of disease and treatments on daily activities and satisfaction with life. Intervention strategies can be formulated by evaluating aspects of quality of life related to health, in order to minimize the effects of the disease of progressive character, and improve aspects of quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…The best quality of life was detected in the emotional domain. It is noticed that the studies have shown conflicting results [10,11]. In this situation, reaffirms the need and relevance of assessing the individual thinking in one and not the collectivity because the being must be evaluated in the context in which is inserted, taking into account their needs, the variables involved in their lives and their daily lives.…”
Section: Discussionmentioning
confidence: 82%
“…Some authors have stated that regardless of the time of surgery, in some domains, women suffer due to the effects of the disease and its treatment [11]. While others, counter that the quality of life can improve as the side effects of therapy are controlled or avoided, and gives importance to knowledge and adherence about complementary therapies, which have helped in coping and treatment of the disease [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emotional support is the most beneficial in the adjustment of women with breast cancer, generating opportunities for them to express feelings and favouring treatment adherence. Spouse has been found out the most important emotional support and the main source of instrumental support [12].…”
Section: Discussionmentioning
confidence: 99%